The Landscape of Copia and Gypsy Retrotransposon During Maize Domestication and Improvement - Zhang, Xiangbo; Qi, Yongwen (Frontiers in Plant Science, 2019)
The release of genomic sequences in the maize HapMap3 population provides an opportunity to study the genetic diversity of maize. In this study, retrotransposon insertion polymorphisms (RIPs) were mapped against the maize genome sequence. In total, 27 retrotransposon families were identified, and more than 170,000 RIPs were discovered in teosinte, landrace, and improved groups. Interestingly, the copy number of transposable elements (TEs) were more abundant in landrace groups than in teosinte or improved groups, suggesting that TEs experienced amplification during domestication and contraction during improvement. Landrace accessions exhibited higher TE insertion frequency compared to the other groups. Furthermore, the position of TE insertions were closer to genes and more abundant in the centromeres of landrace groups compared to the other groups. The three groups could be clearly distinguished by RIPs. These results demonstrate that TEs were amplified and contracted during maize domestication and improvement, respectively.